Isokinetic Muscle Strength and Postural Sway of Recreationally Active Older Adults vs. Master Road Runners - Taveira, Henrique V.; de Lira, Claudio A. B.; Andrade, Marilia S.; Viana, Ricardo B.; Tanaka, Hirofumi; Hill, Lee; Nikolaidis, Pantelis T.; Knechtle, Beat; Rosemann, Thomas; Vancini, Rodrigo L. (Frontiers in Physiology, 2021)
Trunk muscle strength and control is an important prerequisite for everyday activities among elderly people decreasing the predisposition to falls. High levels of physical exercise performed by older athletes could offer benefits to core/trunk muscle strength and postural control compared with recreational physical activities and among elderly people with lower levels of physical activity. The present study aimed to compare trunk muscle strength and postural control of older running athletes vs. older physically active adults. Participants were master road runners (RUN, n=15, 6 women, 64.3±3.6 years) and physically active elderly (control group, CON, n=15, 6 women, 65.4±5.0 years) people that were submitted to the evaluations: esthesiometer, posturography (force plate), and isokinetic test (Biodex dynamometer) of trunk muscle extension and flexion. RUN presented higher values for relative peak torque of trunk extensor muscles at 60º/s (p=0.046) and 180°/s (p=0.007) and relative average power during trunk extension at 60º/s (p=0.008) and 180°/s (p=0.004) compared to CON. CON had a higher medial-lateral oscillation speed of the center of pressure in the stable condition with eyes closed (p=0.004) compared to RUN. RUN presented higher isokinetic torque of extensor trunk muscles and better postural control than CON. This supposedly could help with postural control and balance and contribute to the prevention of falls among the elderly. The practice of running systematically by master athletes may partially explained our findings.